Asymmetric faces: Symbolic, spiritual, and representative. Issue 2 (13th May 2021) - Scheuerle, Angela E.; Firth, Roswitha Mohs
Abstract: In humans, physically attractive faces are measurably, though subtly, asymmetric. As asymmetry increases, it has a negative impact. Medically, asymmetry can be congenital or acquired. Symbolically, it has varied connotations from playfulness and complexity to despair and corruption. In Chinese opera, stylized make‐up exaggerates the features, and aspects of the "mask" indicate qualities of the character. The asymmetric faces belong to characters who are corrupt, devious, or evil. In the Dan culture of western Africa, performance masks channel spirits in the community. A spirit with asymmetric facial mask exemplifies ugliness and moral failing. The Nasca culture of South America made generic figures of farmers, deities, and so on, but not of individuals. However, there is evidence of mutual influence between the Nasca and the Wari, with whom they traded. A clay figure apparently representing an individual, or at least a very specific recognized persona, is a ball player with facial asymmetry presumably due to injury. Here the message is one of fierceness and strength. The relative rarity of asymmetric facial depictions compared to symmetric ones is cross‐cultural. This implies that asymmetry is special somehow, in all connotations of that term.